Interaction of exopolysaccharide produced by Lactobacillus plantarum YW11 with whey proteins and functionalities of the polymer complex. Issue 12 (27th November 2020) - Zhang, Min; Luo, Tianqi; Zhao, Xiao; Hao, Xiaona; Yang, Zhennai
Abstract: Exopolysaccharide (EPS)‐producing lactic acid bacteria have been widely used in fermented milk, but interaction between the EPS and milk proteins has not been well studied. In this study, interaction between the EPS from Lactobacillus plantarum YW11 (EPS‐YW11) and whey proteins (WP), and functional properties of the EPS‐YW11/WP were investigated. The results showed that EPS‐YW11 tended to encase WP by ζ‐potential analysis with a decrease in the surface charge of the protein fraction (from −26.00 mV to 15.30 mV), and an increase in the melting temperature of the protein fraction (from 76.31 °C to 84.48 °C) as shown by differential scanning calorimetry. Circular dichroism spectrometry showed that the EPS could induce structural change of WP, that is, increment in the content of α‐helixes and random coils, There was stronger interaction between EPS‐YW11 and WP at higher temperatures (60 °C,  90 °C) due to formation of intermolecular H‐bonds and OH stretching vibration as indicated by infrared spectral analysis. A significant improvement in the texture (hardness, springiness, gumminess, resilience, cohesiveness, and chewiness) of the EPS‐YW11/WP complex was also observed when compared to that of the EPS or WP alone. This was confirmed by microstructural observation of the EPS‐YW11/WP complex that formed branched and porous structures, and it became more complex and stable with increased temperature treatment. Due to the strong interaction the EPS‐YW11/WP exhibited improved functionality. This study identifies the potential of the EPS‐YW11 to serve as a functional agent in the processing of fermented dairy products with enhanced textural stability and bioactivities such as cholesterol‐lowering, antioxidant, and antibiofilm.